Does Severe Ankle Deformity Affect the Outcomes of a 4th Generation Total Ankle Prosthesis? A 2- Year Follow-Up. Issue 4 (November 2022) - Gross, Christopher E.; Friscia, David A.; Doty, Jesse F.; Vora, Anand M.; Strasser, Nicholas L.
Category: Ankle Arthritis Introduction/Purpose: Fourth generation ankle replacements benefit from improved surgical technique, respect for bony preservation, and increased surgeon awareness of operative indications. In some studies, pre-operative degree of deformity has been reported to influence survivorship, pain, and functional outcomes. The purpose of this multi-institutional study was to evaluate whether pre- operative deformity affects prospectively collected patient reported outcome measures (PROMs) of a fourth-generation total ankle replacement. Methods: Patients presenting for a total ankle replacement at 9 institutions were prospectively enrolled and implanted in a variety of academic and private settings. Each patient received an INFINITY ankle prosthesis. (Styker, Memphis, TN, USA). The degree of deformity was radiographically classified pre-operatively as severe if ankle varus or valgus was greater than 10° in the coronal plane. PROMs were recorded pre-operatively and at 6 months, 12 months, and 24-month intervals. The following PROMs were collected: Ankle Osteoarthritis Score (AOS), PROMIS Global Physical Health, and Foot and Ankle Outcome Score (FAOS). The preoperative and latest follow-up scores for patients with two years of follow-up were analyzed. Results: A total of 147 patients were enrolled in the study. Fifty-two patients exhibited a pre-operative ankle deformity of greater than 10° varus or valgus. Eighty-eight patients had 24 months of follow-up. All patients with severe deformity had significant improvements in all domains of the AOS, PROMIS, and FAOS Scores (p<0001). The degree of deformity, ankle instability, or hindfoot arthritis did not impact the PROMs (AOA p=.2661, PROMIS p=.543, FAOS p=.684) in those with 2-year follow-up.There were three revisions with varying degrees of deformity. Two patients had revisions for aseptic loosening (6o valgus and 10o varus). One patient had a revision for tibial subsidence (11o varus). Conclusion: Severe pre-operative deformity did not impact PROMs in patients undergoing implantation with a 4th generation total ankle replacement. In carefully selected patients, greater deformity did not necessarily correlate with an increased need for revision surgery.